A Dynamic Mass Redistribution Assay for the Human Sweet Taste Receptor Uncovers G-Protein Dependent Biased Ligands - Servant, Nicole B.; Williams, Mark E.; Brust, Paul F.; Tang, Huixian; Wong, Melissa S.; Chen, Qing; Lebl-Rinnova, Marketa; Adamski-Werner, Sara L.; Tachdjian, Catherine; Servant, Guy (Frontiers in Pharmacology, 2022)
The sweet taste receptor is rather unique, recognizing a diverse repertoire of natural or synthetic ligands, with a surprisingly large structural diversity, and with potencies stretching over more than 6 orders of magnitude. Yet, it is not clear if different cell-based assays can faithfully report the relative potencies and efficacies of these molecules. Indeed, up to now, sweet taste receptor agonists have been almost exclusively characterized using cell-based assays developed with overexpressed and promiscuous G proteins. This non-physiological coupling has allowed the quantification of receptor activity via phospholipase C activation and calcium mobilization measurements in heterologous cells on a FLIPR system, for example. Here, we developed a novel assay for the human sweet taste receptor where endogenous G proteins and signaling pathways are recruited by the activated receptor. The effects of several sweet taste receptor agonists and other types of modulators were recorded by measuring changes in dynamic mass redistribution (DMR) using an Epic® reader. Potency and efficacy values obtained in the DMR assay were compared to those results obtained with the classical FLIPR assay. Results demonstrate that for some ligands, the two assay systems provide similar information. However, a clear bias for the FLIPR assay was observed for one third of the agonists evaluated, suggesting that the use of non-physiological coupling may influence the potency and efficacy of sweet taste receptor ligands. Further investigation suggests that the C-terminal tail residues of G subunits play a role in directing bias of ligands for one assay versus the other.